Measuring implementation of risk management using iso 31000 at pt angkasa pura ii (persero) (case study at sultan syarif kasim ii international airport, pekanbaru) - Marthalius, Anton; Aldianto, Leo (The Indonesian Journal of Business Administration, 2016)
Abstract - In running a company, management is inseparable from risk exposure moreover the nature of activities in PT Angkasa Pura II (Persero) that run an airport management business. To effectively manage risk the company required to implement a good Enterprise Risk Management (ERM). As part of the Risk Management implementation process, PT Angkasa Pura II (Persero) has formulated Risk Management Guidelines (Manual) and has implemented policies and risk control measures. However, PT Angkasa Pura II (Persero) still needs to conduct comprehensive evaluation ofÂ  Risk Management in order to get and ideal of the company risk management maturity level. Risk Management maturity level analysis can be conducted through degree of maturity level by using Risk and Insurance Management Society (RIMS) methods for Enterprise Risk Management (ERM). These research is an explanatory research that used qualitative and quantitative analysis. The data processed in this research is primary data through survey, questionnaire, interview and secondary data through data of the existing risk management process in the company. By measuring the existing value of risk management implementation maturity level, it is expected that PT Angkasa Pura II (Persero) espesialy at Sultan Sayrif Kasim II International Airport, Pekanbaru can determine whether the implementation of risk management is effective or not and then this research can generate recommendation for improvements so the implementation of risk management maturity level is in accordance with the desired target from the management. Â Keywords: Risk Management Implementation, ISO 31000, Risk Management Maturity Level, Risk and Insurance Management Society (RIMS).